Free energy approach to micellization and aggregation: Equilibrium, metastability, and kinetics. (April 2016) - Diamant, Haim; Andelman, David
Abstract: We review a recently developed micellization theory, which is based on a free-energy approach and offers several advantages over the conventional one, based on mass action and rate equations. As all the results are derived from a single free-energy expression, one can adapt the theory to different scenarios by merely modifying the initial expression. We present results concerning various features of micellization out of equilibrium, such as the existence of metastable aggregates (premicelles), micellar nucleation and growth, transient aggregates, and final relaxation toward equilibrium. Several predictions that await experimental investigation are discussed. Abstract :